If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 6 = (n + 8) + -7n Reorder the terms: 6 + 6n = (n + 8) + -7n Reorder the terms: 6 + 6n = (8 + n) + -7n Remove parenthesis around (8 + n) 6 + 6n = 8 + n + -7n Combine like terms: n + -7n = -6n 6 + 6n = 8 + -6n Solving 6 + 6n = 8 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 6 + 6n + 6n = 8 + -6n + 6n Combine like terms: 6n + 6n = 12n 6 + 12n = 8 + -6n + 6n Combine like terms: -6n + 6n = 0 6 + 12n = 8 + 0 6 + 12n = 8 Add '-6' to each side of the equation. 6 + -6 + 12n = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 12n = 8 + -6 12n = 8 + -6 Combine like terms: 8 + -6 = 2 12n = 2 Divide each side by '12'. n = 0.1666666667 Simplifying n = 0.1666666667
| 1+sqrt(x+5)=sqrt(2x+5) | | (12a^4b-7a^2b^2+8ab^3)+(-6a^4b-5a^2b^2+3ab^3)= | | 2x-4+7=3 | | (x-4)(x-8)=5 | | 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 | | K+6K-13=57 | | 3x*3x-2x+7=0 | | 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 |